Exploring the perceptions and experiences of medical students in the care for patients diagnosed with COVID-19: A qualitative content analysis - Rahimian, Zahra; Feili, Afrooz; Ardekani, Ali; Janghorban, Roksana (Iatreia, 2022)
Introduction: Medical students faced numerous problems to combat the COVID-19 pandemic as the least experienced medical staff members. Awareness of the impact of the COVID-19 pandemic on medical students is essential to manage and control its adverse effects. Objective: This study aimed to explore medical students’ perceptions and experiences during the COVID-19 pandemic. Methods: We conducted a qualitative study in May and June 2020 involving semi-structured phone interviews with 19 medical students. Data were collected through in-depth telephone interviews and analyzed with MAXQDA 10 software using the conventional content analysis proposed by Graneheim and Lundman. Results: Thirty subcategories, six categories, and three themes emerged from the data analysis. The themes included perceived mental and emotional paradox (pleasurable feelings complicated by negative feelings and emotions), encountering catastrophe (being confronted with a lack of equipment and disorganized management; working in turmoil), and attempting to adapt to unpleasant conditions (individual efforts toward psychological adjustment; attempting to resile as a professional). Conclusion: The COVID-19 pandemic had multiple positive and negative emotional, educational, and occupational effects on medical students. This study highlighted these effects by exploring the students’ experiences. Design of an organized pandemic response plan for medical student is recommended in various aspects of education, patient care and coping skills for future pandemics.